A Rhenium‐Functionalized Metal–Organic Framework as a Single‐Site Catalyst for Photochemical Reduction of Carbon Dioxide. Issue 27 (5th April 2016) - Huang, Ruiyun; Peng, Yu; Wang, Cheng; Shi, Zhan; Lin, Wenbin
Abstract : A metal–organic framework (MOF) based on (bpy)Re(CO)3 Cl‐containing elongated dicarboxylate ligands and Zr6 (µ3 ‐O)4 (µ3 ‐OH)4 clusters was synthesized and used as an effective single‐site catalyst to photochemically reduce carbon dioxide to carbon monoxide and formate and to provide mechanistic insights into the photocatalytic CO2 reduction process. Abstract : A (bpy)Re(CO)3 Cl‐containing metal–organic framework (MOF) acts as an effective single‐site catalyst to photochemically reduce carbon dioxide to carbon monoxide and formate. Mechanistic insights into the monomolecular pathway of the photocatalytic CO2 reduction have been obtained without interference from bimolecular pathways, thanks to site‐isolation of the catalytic centers in MOFs.